(untitled) (Journal of the College of Basic Education, 2022)
In this study the effect of Nagellia sativa seed oil was studied on cytopathic effect which result from injection number of mice intraperitonial with suspension of Staphylococcus aureus, these mice previously orally administrated with concentration 50 % of N. sativaoil, another mice group were injected with bacterial suspension without previously administrated with seed oil, the results were showed the cytopathic effect of S. aureus suspension on organs of mice that which administrate orally with N. sativaseed oil were lessthan effect of bacterialsuspension on organs of animal which don’t previously administrated with seed oil.